Polarization characteristics of radiation in both ‘light’ and conventional undulators; Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms; Vol. 402 - Potylitsyn A. P. Alexander Petrovich (2017, 2017)
Title screen